THE USE OF BANDICAM APPLICATION AS TEACHING MEDIA TO ENHANCE STUDENTS’ WRITING SKILL - Siska Azurah; Hj Nurfaisah Sahib; Andi Hamzah Fansury (THE ACADEMIC: ENGLISH LANGUAGE LEARNING JOURNAL, 2022)
This research aimed to know whether the use of the bandicam application as a teaching media can enhance students' writing skill in SMAN 18 Makassar.This research focused on pre-experimental research one group pretest and posttest. The population of this research was the tenth-grade students of SMAN 18 Makassar at the first semester 2021/2022 academic year. The writer took of 270 students as population. The data were obtained from the writing text. The results of the research used inferential analysis of t-test by SPSS v.16, showed that there was a significant enhance in the students’ mean score writing skill between the pretest and posttest. The mean score of the students’ writing enhanced from 51.04 in the pretest to 79.95 in the posttest. The significance value calculated 0.000 is smaller than 0.05 (P-value = 0.000 < 0.05). Therefore, the hypothesis of this study was accepted. It means that the use Bandicam Application As Teaching Media Can Enhance students writing skill at SMAN 18 Makassar. In addition, students' motivation after using this media also increased. The writer concluded that the use of Bandicam Application As Teaching Media in teaching English can enhance the students’ writing skill.